THE USE OF TIKTOK EDUCATIONAL CONTENT AS MEDIA FOR LEARNING ENGLISH PRONUNCIATION - HS, Firdayanti; Muliati, A.; Ariyani, Amra (Universitas Negeri Makassar, 2025)
The objective of this study is to ascertain whether the use of TikTok educational content significantly improves the English pronunciation of seventh-grade students at UPT SPF SMPN 27 Makassar. This research employs a pre-experimental design using a one-group pretest-posttest approach. The sample for this study included 30 Students from class 7.2 who were chosen using a purposive sampling technique. Data collection was conducted through a pre-test, treatment consisting of four sessions, and a post-test. The results indicated that the mean score and standard deviation of the pretest were 46.22, categorized as poor, while the post-test score after treatment was 71.33, categorized as good. The percentage improvement from pretest to post-test was 54.32%. Hypothesis testing results showed a significant difference between the pretest and posttest scores, evidenced by a significance value (2-tailed) of 0.001 < 0.05. This signifies that the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted.